Genetic diversity of Rhizopus microsporus from traditional inoculum of tempeh in Indonesia based on ITS sequences and RAPD marker - TATI BARUS (MBI & UNS Solo, 2019)
Abstract. Barus T, Halim R, Hartanti AT, Saputra PK. 2019. Genetic diversity of Rhizopus microsporus from traditional inoculum of tempeh in Indonesia based on ITS sequences and RAPD marker. Biodiversitas 20: 847-852. The main microorganism for tempeh fermentation is Rhizopus microsporus. These days, many tempeh producers use commercial inoculum, such as ‘Raprima’ as resource of R. microsporus. As a result, the genetic diversity of R. microsporus that had been reported in Indonesia has diminished. Information about genetic diversity is needed as a basis to select R. microsporus as tempeh inoculum. This research aims to investigate the genetic diversity of R. microsporus from waru leaves based on Internal Transcribed Spacer (ITS) Sequence and Random Amplified Polymorphic DNA (RAPD) markers. A total of 25 R. microsporus were isolated from traditional inoculum waru leaves (Inoculum 1) and traditional inoculum other than waru leaves (Inoculum 2). Amplification of ITS sequence was done using universal primer pairs of ITS-4 and ITS-5. Amplification of RAPD markers was done using primers OPC-08, OPC-19, OPQ-6, R-108, OPA-09 and OPJ-20. ITS sequence was not sufficient to compare the similarities among R. microsporus. On the other hand, RAPD markers successfully compared the similarities among 25 R. microsporus. A total of 25 R. microsporus were divided into 9 clusters. R. microsporus from Inoculum 1 grouped into Cluster 1, Cluster 3 and Cluster 4-8. Inoculum 2 grouped into Cluster 2 and Cluster 9. R. microsporus from tempeh grouped into Cluster 4 and was different from Inoculum 1 and Inoculum 2, except for TB3.